ANALISIS MANAJEMEN SEKURUTI PADA OBJEK VITAL NASIONAL BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA - Al Fachri Nurfath; Fried Sinlae (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research was conducted to find out the application of security management concepts to National Vital Objects, such as setting policy guidelines, implementing security controls, monitoring evaluation, to create a safe and controlled environment. In this research the Vital Object that is the object of observation is Soekarno-Hatta International Airport which is located, because this facility is the largest in Indonesia, if the security of this object is disturbed it could result in chaos on a national scale, therefore the researcher wants to see what the security aspects of this vital object are, the research method used this time is Descriptive Qualitative with a Study approach literature, where researchers collect data through reading sources such as books, articles, web pages, which are related to the research topic, after which an output is created based on the data the researcher has collected